KEBIJAKAN PENDIDIKAN ISLAM NONFORMAL BERBASIS DIGITAL SEBAGAI STRATEGI PENGUATAN MODERASI BERAGAMA DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG - Khusnul Mazidah; Ahmad Ubaidil Munfarid; Ainur Rofiq (STKIP Pesisir Selatan, 2026)
This study examines the dynamics of digital-based non-formal Islamic education policies in strengthening religious moderation at Darussalam Islamic Boarding School (Pondok Pesantren Darussalam) Blokagung, Banyuwangi, as a response to the challenges of the digital era. The study aims to analyze the existing policy conditions, identify gaps in digital literacy, and formulate the need for adaptive and contextual policy reconstruction. A qualitative approach with a case study design was employed, involving Islamic boarding school administrators, Islamic teachers (ustadz), and students (santri) as research participants. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and technique triangulation. The findings reveal that the utilization of digital technology in the Islamic boarding school has been implemented in a limited and controlled manner; however, it has not yet been supported by well-structured formal policies. Furthermore, disparities in digital literacy among teachers and students have affected the effectiveness of the learning process. Therefore, an adaptive policy reconstruction is required to systematically integrate digital technology with the values of religious moderation, enabling Islamic boarding schools to remain relevant in the digital era while preserving their Islamic identity.